Growth and physiology of ornamental sunflower under salinity in function of paclobutrazol application methods - Rafaela F. B. Guimarães; Sebastião de O. Maia Júnior; Robson F. de Lima; Allesson R. de Souza; Jailma R. de Andrade; Ronaldo do Nascimento (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The ornamental sunflower has great importance in the floriculture sector due to the color and vitality of its flowers. However, the production and quality of flowers decrease under salt stress, which can be mitigated with paclobutrazol application. The objective of the present study was to evaluate the effects of different application methods of paclobutrazol in ornamental sunflower ‘Sol Noturno’ irrigated with brackish waters. The experimental design was randomized blocks arranged in a 5 × 3 factorial scheme, corresponding to five electrical conductivities of irrigation water - ECw (0.4; 1.9; 3.4; 4.9, and 6.4 dS m-1) and three paclobutrazol application methods (foliar application, via soil and a control treatment - without paclobutrazol), with four replicates. The increase in salinity of irrigation water reduced gas exchange, photosystem II photochemical efficiency, SPAD index, plant height, and chapter diameter. The paclobutrazol application via soil or foliar increased stomatal conductance and transpiration by 21.09 and 17.80%, respectively, in comparison to plants without application, whereas photosynthesis and instantaneous carboxylation efficiency increased by 28.33 and 31.18% via soil and 14.40 and 16.12% via foliar, respectively. The paclobutrazol application, mainly via soil, favored ‘Sol Noturno’ sunflower plants under salt stress, increasing chlorophyll SPAD index and external chapter diameter, and keeping the number of the petals.